MEMBANGUN KUALITAS PEMBELAJARAN MELALUI PRAKTIK REFLEKTIF GURU DI SEKOLAH DASAR - Latri Latri; Muh. Rizah Putrawan; Nurhaedah Nurhaedah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
This study aimed to analyze the effect of teachers’ reflective practices on learning quality through instructional follow-up in elementary schools. The study employed a quantitative approach using a survey method. The respondents consisted of 43 elementary school teachers selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with the assistance of SmartPLS. The findings revealed that teachers’ reflective practices had a positive effect on instructional follow-up and learning quality. Teachers who consistently engaged in reflective practices tended to evaluate the learning process more effectively, improve teaching strategies, and adapt instruction to students’ learning needs. In addition, instructional follow-up was found to positively influence learning quality and mediate the relationship between reflective practices and learning quality.The study indicates that continuous reflective practice can help teachers improve the quality of classroom learning, student engagement, and teacher professionalism. Therefore, reflective practice needs to be strengthened as part of teacher competency improvement and professional development in elementary schools.